International Ratings: Statistical Aspects of Computing and Application. Part II. Indexes of Innovation and Human Development - Yerina, A. M. (Statistics of Ukraine, 2016)
Innovation activity and technological renovation in all the social spheres has become a prime factor behind economic growth and competitiveness in advanced countries of the world. The innovation-driven economy ensures the economic power of a country, lays the ground for human development and high standards of life quality. The strengthening role of the innovation component in the socio-economic development raises the importance of studies on innovation capacities and national innovation systems’ performance. Methods for computation and use of international ratings of innovation-driven development and human development of countries in the context of global information area are highlighted. An important source of data on the development of national innovation systems and their impact on the country’s position in the global system of coordinates is Global Innovation Index (GII). Its computation method is based on combination of innovative capacities and results of innovating. Apart of comparative analysis, GII, based on the rich and singular set of data, allows for identification of relative advantages and weak sides of national innovation systems and offers an important tool for innovation policy assessment at country level. Analysis of Ukraine’s position in GII rating for 2016 gives clear evidence of the irregular and imbalanced development of various components in the national innovation system: whatever is associated with human resources (education, availability of skilled workforce, labor market, patent activity), remains at relatively high level, whereas institutional and organizational components, regulatory framework, innovation activity of companies are not favorable for the innovation-driven development. The contemporary innovation process implies important role of information and communication technologies (ICT), associated with rapid dissemination of radically new patterns for communication, social integration, mode of life, education etc. Monitoring of ICT advancements in various countries, measurement of digital gap, assessment of capacities for ICT development considering the existing opportunities and skills are problems dealt with through constructing the IDI rating – ICT Development Index. As shown by IDI 2016, countries leading by ICT development are ones with high income level, which confirms correlation between income and advancement in ICT. Apart from design and dissemination of new technologies, the innovation-driven development is associated with “innovative” attitude to a human. It is humans with appropriate education, skills or experiences who set up frontiers and resources for technological, economic and social modernization of a society. Rates of economic growth per se, however high, will not ensure the social progress unless the primary conditions for humans exist: to live long and healthy life; to acquire, extend and renew one’s knowledge; to have access to basic necessities sustaining good life standards. An adequate tool for measurement of human development in the global context is Human Development Index (HDI), aggregating prime components of human development: health and longevity, education level, material welfare. Methodological approaches to computation and use of various international ratings, highlighted in the article, illustrate the rich arsenal of statistical methods for standardization and convolution of indicators and analytical capacities of integral estimates. Each index carries its analytical mission; each one is constructed by its set of basic indicators and has its singular computation methodology. The massive base of systematized data, enabling for quick identification of strong and weak sides of national capacities, can be used for making informed managerial decisions.